The problem of stagflation : reflections on the microfoundation of macroeconomic theory and policy - Haberler, Gottfried (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1985)
This book examines the dilemma stagflation poses for macroeconomic policy. It shows how attempts to curb inflation through tight monetary and fiscal policies increase unemployment, and attempts to reduce unemployment through easy money accelerate inflation.
Includes bibliographies.
usc 13/06/18
Loans
Keywords: Unemployment; Unemployment--Effect of inflation